On the potential for using immersive virtual environments to support laboratory experiment contextualisation - Machet, T.; Lowe, D.; Guetl, Christian (Taylor & Francis, 2012)
This paper explores the hypothesis that embedding a laboratory activity into a virtual environment can provide a richer experimental context and hence improve the understanding of the relationship between a theoretical model and the real world, particularly in terms of the model’s strengths and weaknesses. While an identified learning objective of laboratories is to support the understanding of the relationship between models and reality, the paper illustrates that this understanding is hindered by inherently limited experiments and that there is scope for improvement. Despite the contextualisation of learning activities having been shown to support learning objectives in many fields, there is traditionally little contextual information presented during laboratory experimentation. The paper argues that the enhancing laboratory activity with contextual information affords an opportunity to improve students’ understanding of the relationship between the theoretical model and the experiment (which is effectively a proxy for the complex real world), thereby improving their understanding of the relationship between the model and reality. The authors propose that these improvements can be achieved by setting remote laboratories within context-rich virtual worlds.